Growth of free-standing wurtzite AlGaN by MBE using a highly efficient RF plasma source - Novikov, Sergei V.; Staddon, Chris R.; Whale, Josh; Kent, Anthony J.; Foxon, C. Thomas (AIP, 2016)
Ultraviolet light emitting diodes (UV LEDs) are now being developed for various potential applications including water purification, surface decontamination, optical sensing, and solid-state lighting. The basis for this development is the successful production of AlxGa1_xN UV LEDs grown by either metal-organic vapor phase epitaxy (MOVPE) or molecular beam epitaxy (MBE). Initial studies used mainly sapphire as the substrate, but this result in a high density of defects in the epitaxial films and now bulk GaN or AlN substrates are being used to reduce this to acceptable values. However, the lattice parameters of GaN and AlN are significantly different, so any AlGaN alloy grown on either substrate will still be strained. If, however, AlGaN substrates were available, this problem could be avoided and an overall lattice match achieved. At present, the existing bulk GaN and AlN substrates are produced by MOVPE and physical vapor transport, but thick freestanding films of AlGaN are difficult to produce by either method. The authors have used plasmaassisted MBE to grow free-standing AlxGa1_xN up to 100 lm in thickness using both an HD25source from Oxford Applied Research and a novel high efficiency source from Riber to provide active nitrogen. Films were grown on 2- and 3-in. diameter sapphire and GaAs (111)B substrates with growth rates ranging from 0.2 to 3 lm/h and with AlN contents of 0% and _20%. Secondary ion mass spectrometer studies show uniform incorporation of Al, Ga, and N throughout the films, and strong room temperature photoluminescence is observed in all cases. For films grown on GaAs, the authors obtained free-standing AlGaN substrates for subsequent growth by MOVPE or MBE by removing the GaAs using a standard chemical etchant. The use of high growth rates makes this a potentially viable commercial process since AlxGa1_xN free-standing films can be grown in a single day and potentially this method could be extended to a multiwafer system with a suitable plasma source.